Low-level mosaic trisomy 14 at amniocentesis in a pregnancy associated with cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, positive non-invasive prenatal testing for trisomy 14, perinatal progressive decrease of the trisomy 14 cell line and a favorable fetal outcome - Chih-Ping Chen; Fang-Tzu Wu; Shu-Yuan Chang; Peih-Shan Wu; Yen-Ting Pan; Meng-Shan Lee; Chien-Ling Chiu; Wayseen Wang (Elsevier, 2024)
Objective: We present low-level mosaic trisomy 14 at amniocentesis. Case report: A 37-year-old, gravida 2, para 1, woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. This pregnancy was conceived by in vitro fertilization and embryo transfer (IVF-ET). Amniocentesis revealed a karyotype of 47,XX,+14 [4]/46,XX [27], consistent with 12.9% mosaicism for trisomy 14. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (1-22, X) × 2 with no genomic imbalance. Prenatal ultrasound findings were unremarkable. She was referred for genetic counseling at 21 weeks of gestation and was offered expanded non-invasive prenatal testing (NIPT) which was positive for trisomy 14. At 24 weeks of gestation, she underwent repeat amniocentesis which revealed a karyotype of 47,XX,+14 [2]/46,XX [26], consistent with 7% mosaicism for trisomy 14. The parental karyotypes were normal. Simultaneous aCGH analysis on the DNA extracted from uncultured amniocytes revealed no genomic imbalance. Polymorphic marker analysis excluded uniparental disomy (UPD) 14. Interphase fluorescence in situ hybridization (FISH) analysis on 104 uncultured amniocytes detected no trisomy 14 cell. At 35 weeks of gestation, a 2315-g phenotypically normal baby was delivered. The umbilical cord and placenta had the karyotype of 46, XX (40/40 cells). aCGH analysis on the DNA extracted from peripheral blood and buccal mucosal cells at the age of three months revealed no genomic imbalance. The neonate was normal in phenotype and development during postnatal follow-ups. Conclusions: Low-level mosaic trisomy 14 at amniocentesis can be associated with cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, perinatal progressive decrease of the trisomy 14 cell line and a favorable fetal outcome.